Innovative Technological Materials Structural Properties by Neutron Scattering, Synchrotron Radiation and Modeling - Skrzypek, Jacek J.; Rustichelli, Franco; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book provides at first ideas on the answers that neutrons and Synchrotron Radiation could give in innovative materials science and technology. In particular, non-conventional, unusual or innovative neutron and x-ray scattering experiments (from both the scientific and the instrumental point of view) will be described which either have novel applications or provide a new insight into material science and technology. Moreover, a capability of the existing and the enhanced constitutive models and numerical procedures to predict complex behaviour of the novel multifunctional materials is examined.
and State-of-the-Art -- X-ray and Neutron Scattering -- Microstructural Investigations by Small Angle Scattering of Neutrons and X-rays -- Residual Stress Analysis by Neutron and X-ray Diffraction -- Three-Dimensional Imaging by Microtomography of X-ray Synchrotron Radiation and Neutrons -- Constitutive Models for Analysis and Design of Multifunctional Technological Materials -- Enhanced Numerical Tools for Computer Simulation of Coupled Physical Phenomena and Design of Components Made of Innovative Materials.
Keywords: Physics; Crystallography; Materials; Physics; Solid State Physics; Spectroscopy and Microscopy; Materials Science, general; Continuum Mechanics and Mechanics of Materials; Crystallography